2019
DOI: 10.1093/heapro/daz083
|View full text |Cite
|
Sign up to set email alerts
|

Space-time analysis of unhealthy food advertising: New Zealand children’s exposure and health policy options

Abstract: Summary Reducing children’s exposure to unhealthy food advertising is an accepted strategy to end childhood obesity. This study aimed to (i) measure children’s space-time exposures to unhealthy food advertising in public outdoor spaces, using GPS and wearable cameras; and (ii) test effectiveness of banning options. We compiled data (collected July 2014—June 2015) on 138 12-year-old children in Wellington, New Zealand, using wearable cameras and GPS devices worn over 4 days. In 2017–18, we linked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 21 publications
1
21
0
Order By: Relevance
“…protein, vegetables and fibre) and offsets these against the undesirable nutrients, which can lead to some classifications that appear counterintuitive (such as McDonalds fries being healthy). Foods not permitted by the WHO Euro NPM have consistently made up a majority of food advertisements outdoors, with previous studies reporting 50•2 % (23) and 89•2 % (55) , and, in the present study, 79•5 %.…”
Section: Discussionsupporting
confidence: 79%
“…protein, vegetables and fibre) and offsets these against the undesirable nutrients, which can lead to some classifications that appear counterintuitive (such as McDonalds fries being healthy). Foods not permitted by the WHO Euro NPM have consistently made up a majority of food advertisements outdoors, with previous studies reporting 50•2 % (23) and 89•2 % (55) , and, in the present study, 79•5 %.…”
Section: Discussionsupporting
confidence: 79%
“…Of the 36 included studies, 28 reported on the prevalence of unhealthy advertising in outdoor spaces or on publicly owned assets 33–60 ; two reported associations between outdoor marketing and consumption of unhealthy food 6,61 ; one reported associations between outdoor advertising and the school food environment 58 ; one reported outdoor advertising and neighborhood level obesity rates 62 ; two reported on policy options for regulating unhealthy food marketing in outdoor environments 63,64 ; two reported on public opinions towards marketing regulation 65,66 ; and one study reported an evaluation of Chile’s Law of Food Labeling and Advertising 67 . A detailed description of all included studies from the academic literature is reported in Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies reported on outdoor advertising specifically in areas surrounding schools. These studies, undertaken in various countries (Australia, 44,52,53 New Zealand, 39,42,46,49,58 Canada, 57 the USA, 41,43 and Manila, The Philippines, and Ulaanbaatar, Mongolia 45 ), consistently showed that unhealthy food and beverage advertising is prevalent in areas around schools. For example, one Australian study of advertisements within a 500-m radius of primary schools in Sydney and Wollongong found that 80% of food and beverage advertisements were promoting unhealthy food, beverages and alcohol.…”
Section: Prevalence Of Unhealthy Food Advertising In Outdoor Environm...mentioning
confidence: 96%
“…Overall, children tend to be neglected in these studies (Ravensbergen et al, 2016). Recent exceptions include research in New Zealand using GPS and wearable cameras to measure children's space-time exposures to unhealthy food advertising in public outdoor spaces and Google street view to identify the types of advertising across the built environment (Liu et al, 2019;Egli et al, 2019); and in Beirut and Tunis, testing out wearable cameras as a measure of exposure to obesogenic environments (Semaan et al, 2020). An earlier study in Canada used activity-travel log approach to identify children's "activity spaces" beginning and ultimately ending at home in relation to fast food outlet exposure (Ravensbergen et al, 2016).…”
Section: Step 4: Measure the Food Environments Surrounding Children Amentioning
confidence: 99%